Hubungan Pengetahuan tentang Bahaya Merokok dengan Perilaku Merokok Siswa SMP Negeri 2 Lubuk Alung - Yulia M. Nur; Novriani Husna; Rosmanidar Rosmanidar (Universitas Baiturrahim, 2022)
Smoking is a behavior that is harmful to health. Smoking can also have a negative impact on people who are around smokers. The risk to be borne by passive smokers is more dangerous than active smokers because resistance to harmful substances is very low. Cigarettes contain 4000 chemicals with 200 types of which are carcinogenic, this toxic material is found in the main smoke, namely cigarette smoke that is inhaled directly into the smoker's lungs and side smoke, namely the smoke produced by the burning tip, for example carbon monoxide, benzopyrene, and ammonia. Factors that can influence smoking behavior; One of them is knowledge. This study aims to determine the relationship between knowledge about the dangers of smoking and smoking behavior in students of SMPN 2 Lubuk Alung in 2019. This study used an analytical survey method research design with a cross sectional study approach. The population of this study were all male students who attended SMPN 2 Lubuk Alung. The number of population in this study was 57 people. The sampling technique used a sampling technique in the form of random sampling. The results showed 54.4% of respondents had less knowledge about the dangers of smoking, 59.6% of respondents had smoking behavior including the category of smokers. The relationship between knowledge about the dangers of smoking and smoking behavior was p = 0.003 or p <0.05.